21-gene recurrence score testing utilization among older women from different races: A population-based study. Issue 2 (March 2021) - Gulbahce, H. Evin; White, Sandra; Herget, Kimberly A.; Stoddard, Greg; Camp, Nicola J.; Buys, Saundra S.; Sweeney, Carol
Abstract: Objectives: The influence of older age at diagnosis in combination with race/ethnicity on utilization and results of the 21-gene recurrence score (RS) assay for breast cancer (BC) patients is not fully understood. Our objectives were to evaluate the utilization of RS among older women with BC, the likelihood of a high-risk RS, and factors associated with breast cancer-specific mortality (BCSM) among older patients across different races. Materials and methods: We utilized the Surveillance, Epidemiology, and Results (SEER) database with linked RS results to evaluate women with estrogen receptor-positive BC diagnosed 2004–2015. Multivariable logistic regression was used to describe the differences in utilization of RS testing and the association of high-risk RS according to patient characteristics. The Cox proportional hazards model was used to analyze factors associated with BCSM. Results: We found that 20.4% (109, 244/536, 555) of all women ≥18 and 14.3% (33, 584/235, 171) of women ≥65 underwent RS testing. Non-whites had lower odds of RS testing at younger ages whereas among women ≥65 there was no significant difference. After taking into account stage and grade, being ≥65 reduced the odds of high-risk RS in all races except American Indian/Alaskan Native. Age ≥ 65 was independently associated with increased hazard BCSM. Among women ≥65 with high-risk RS, chemotherapy was associated with lower hazard of BCSM in all races. Conclusions: Older women are less likely to be tested for RS, but also less likely to have high-risk RS. Older women with high-risk RS, when given chemotherapy have reduced BCSM across all races.